"I'm not sure whether I died that day or had been resurrected." Paschal themes in Irit Amiel's stories. Issue 3 (3rd July 2021) - Regiewicz, Adam
ABSTRACT: Irit Amiel is an Israeli writer who writes about the Shoah, after almost 50 years of silence since having been rescued from it. Her stories are a collection of portraits in modest narratives. Until now, little attention has been paid specifically to the thread of biblical tradition in texts dedicated to the Holocaust. This article is an attempt to read Amiel's short stories through readings from the Midrash from a messianic perspective. The method of reading is based on the concept of loci theologici, derived from the semiotics and traditions of the sacred. We cannot therefore escape it while reading texts concerning the Holocaust.